Viral infections as environmental factors in the pathogenesis of selected autoimmune diseases - Szafraniec, Artur; Szczotka, Dominika; Krężel, Olga; Krężel, Maciej (Journal of Education, Health and Sport, 2025)
Autoimmune diseases are conditions in which the immune system loses its ability to distinguish between self and foreign antigens, leading to tissue damage and chronic inflammation. Their development is the result of the interaction of genetic, environmental, hormonal, and immunological factors. Viral infections play a particularly important role, as they can initiate autoimmunity through mechanisms such as molecular mimicry, epitope expansion, or non-specific lymphocyte activation. The viruses most commonly associated with the development of autoimmunity include Epstein-Barr virus (EBV), Coxsackie B, HHV-6, HIV, and other. Examples of diseases in which such relationships are observed include type 1 diabetes, systemic lupus erythematosus, multiple sclerosis, rheumatoid arthritis, and psoriasis. Although standard vaccinations do not protect against the onset of autoimmune diseases, they are an important part of preventing infections that can exacerbate their course. A promising area of research is tolerogenic vaccines, which aim to restore tolerance to autoantigens. Preclinical and early clinical studies demonstrate their safety and ability to modulate the immune response, opening up new perspectives in the treatment of autoimmune diseases.